Analisis Pendapatan Petani Belimbing (Averhoa carambola) Di Desa Durin Simbelang Kecamatan Pancur Batu Kabupaten Deli Serdang - Situmorang, Sudirman; Ilvira, Rika Fitri (Universitas Medan Area, 2025)
The natural conditions of Indonesia with different climate potentials and altitudes provide great potential for developing tropical fruits. Starfruit is widely found in tropical areas and is very popular among the community, especially in Durin Simbelang Village, Pancur Batu District. The purpose of this study was to determine the cost structure, revenue and income of starfruit farmers. This study used a purposive sampling method in the form of a census of starfruit farmers, namely 23 people and the determination of the research location was deliberate because this area is one of the starfruit producing areas in North Sumatra which is known for its starfruit quality. The data collection methods used were questionnaires and field observations. The data analysis tools used were cost, revenue and income structures. The results of this study obtained an average starfruit production of 4,691 kg / harvest season with a selling price of Rp. 5,000 / kg so that the average income obtained was Rp. 23,456,521. The cost of expenditure per harvest season was Rp. 3,025,305, so from these costs the average income of starfruit farmers was Rp. 20,431,216. In farming, the income obtained by star fruit farmers can be said to be high.